2019
DOI: 10.3390/v11030249
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Levels of Peste Des Petits Ruminants (PPR) Virus in Excretions from Experimentally Infected Goats and Its Importance for Nascent PPR Eradication Programme

Abstract: Following the successful eradication of rinderpest, the World Organization of Animal Health (OIE) and the Food and Agriculture Organisation (FAO) have set a goal to globally eradicate Peste des petits ruminants (PPR) by 2030. To support the eradication programme we have quantified the levels of PPR virus (PPRV) nucleic acid excreted in body fluids (blood, feces, saliva, nasal and eye swabs) of PPRV-infected goats to ascertain which days post-infection animals are potentially infectious, and hence direct quaran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 28 publications
4
34
0
Order By: Relevance
“…In this study, conjunctival swabs were used in PPRV-RDT. However, a recent experimental infection study that compared the use of conjunctival and nasal swabs for PPRV RT-qPCR demonstrated that nasal swabs were superior for the detection of PPRV nucleic acids from two days post-infection to Viruses 2020, 12, 389 22 of 27 14 days post-infection when the study ended [27]. Therefore, nasal samples may be preferable for PPRV-RDT in order to detect the disease during outbreak investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, conjunctival swabs were used in PPRV-RDT. However, a recent experimental infection study that compared the use of conjunctival and nasal swabs for PPRV RT-qPCR demonstrated that nasal swabs were superior for the detection of PPRV nucleic acids from two days post-infection to Viruses 2020, 12, 389 22 of 27 14 days post-infection when the study ended [27]. Therefore, nasal samples may be preferable for PPRV-RDT in order to detect the disease during outbreak investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Two live attenuated PPR vaccine viruses, PPRV/Nigeria 75/1 and PPRV/Sungri 96 (written as Nigeria 75/1 and Sungri 96, respectively throughout this paper), were used to vaccinate the animals in this study. The challenge viruses used were PPRV/Morocco/2008 and PPRV/Ghana/78 as described previously [13]. Cells at about 60%-70% confluency were infected with the vaccine viruses at an multiplicity of infection (MOI) of 0.1 and incubated at 37 • C with 5% CO 2 .…”
Section: Cells and Virusesmentioning
confidence: 99%
“…Total RNA was extracted from the clinical material (nasal, mouth, and eye swabs, and EDTA-blood) as described previously [13] and stored at −70 • C as single-use aliquots until tested. All samples were analyzed by real-time RT-PCR (RT-qPCR) to detect the presence of PPRV nucleic acid [17] using the Superscript III Platinum R one step qRT-PCR system kit (Invitrogen, Carlsbad, CA, USA)) on the ABI 7500 system (Applied Biosystems, Paisely, UK).…”
Section: Rna Extraction and Detection Of Pprv Nucleic Acid In Blood Amentioning
confidence: 99%
“…All the field samples were of goat origin except for three ocular and three nasal swabs (samples 5–7 and 10–12 in Table 1) that were collected from sheep. In addition, clinical materials such as a nasal swab, faecal samples and various tissues collected from goats experimentally infected with PPRV (Morocco/2008 or Ghana/78) at TPI were also included [22]. Furthermore, filter papers impregnated with virus samples (cell culture supernatant) were also included to account for samples that are usually collected in the field as filter paper spots and later transported to the laboratory for diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted from PPRV infected cell culture supernatant, EDTA blood and animal tissues using TRIzol reagent (Invitrogen, Carlsbad, CA, USA) as described previously [19]. In addition, total RNA was also extracted from milk samples [20]; ocular and nasal swabs collected from sheep and goats in Tanzania [18]) and nasal swabs and faecal samples from experimentally-infected animals [22]. The filter papers impregnated with PPRV were placed in a 1.5 mL microcentrifuge tube containing 200 μL of RNase-free water and incubated at room temperature for ~10 min before being centrifuged at 3000× g for 5 min.…”
Section: Methodsmentioning
confidence: 99%